Morality in a natural world: selected essays in metaethics - Copp, David (Cambridge studies in philosophy, 2007)
Introduction -- Naturalism : epistemology, and metaphysics -- Why naturalism? -- Four epistemological challenges to ethical naturalism : naturalized -- Epistemology and the first-person perspective -- Moral naturalism and self-evident moral truths -- Moral necessities in a contingent world -- Referring to moral properties -- Realist-expressivism : a neglected option for moral realism -- Milk, honey, and the good life on moral twin earth -- Referring to moral properties : moral twin-earth, again -- Naturalism and normativity -- Moral naturalism and three grades of normativity -- The ring of gyges : overridingness and the unity of reason -- The normativity of self-grounded reason